2005
DOI: 10.1111/j.1471-4159.2005.03445.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKC‐α,γ isoforms in regulation of c‐Fos and TH expression after naloxone‐induced morphine withdrawal in the hypothalamic PVN and medulla oblongata catecholaminergic cell groups

Abstract: We previously demonstrated that morphine withdrawal induced hyperactivity of the hypothalamus-pituitary-adrenocortical axis by activation of noradrenergic pathways innervating the hypothalamic paraventricular nucleus (PVN), as evaluated by Fos expression and corticosterone release. The present study was designed to investigate the role of protein kinase C (PKC) in this process by estimating changes in PKCa and PKCc immunoreactivity, and whether pharmacological inhibition of PKC would attenuate morphine withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
7
13
0
Order By: Relevance
“…Previous reports from our laboratory indicate that inhibition of PKC significantly blocked the corticosterone secretion during morphine withdrawal (50). These findings are consistent with the observation that PKC is up-regulated in the PVN during morphine dependence and may suggest that PKC activity is necessary for the increased HPA axis activity during morphine withdrawal (41).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous reports from our laboratory indicate that inhibition of PKC significantly blocked the corticosterone secretion during morphine withdrawal (50). These findings are consistent with the observation that PKC is up-regulated in the PVN during morphine dependence and may suggest that PKC activity is necessary for the increased HPA axis activity during morphine withdrawal (41).…”
Section: Discussionsupporting
confidence: 87%
“…Recent findings from our group have also shown the involvement of an up-regulated cAMP-dependent protein kinase A in activating TH levels and c-Fos expression in the NTS during morphine withdrawal (40). In addition, we have also shown that activated PKC may be critical for the activation of the catecholaminergic brain stem cell groups in response to opioid withdrawal (41). In the present study, it should be noted that TH protein expression was increased in NTS in morphine dependent rats, suggesting that the effect of morphine is mediated through both the activation (via phosphorylation) of TH and the up-regulation of its expression, which is in agreement with previous results from this laboratory (14).…”
Section: Discussionmentioning
confidence: 74%
“…2008) whereas chronic perfusion with calphostin C reported clear inhibition of morphine withdrawal‐induced neuroendocrine changes in rats (Cerezo et al. 2002; Benavides et al. 2005).…”
Section: Methodsmentioning
confidence: 99%
“…We observed a partial colocalization (laminae I-II), suggesting that pERK1/2 could contribute to c-Fos expression in our in vivo model. However, a similar number of c-Fos-positive neurons did not coexpress pERK1/2, indicating that alternative pathways such as protein kinase A, protein kinase C, and p38 kinase could also regulate c-Fos expression (Benavides et al, 2005;Svensson et al, 2005;Gonzá lez-Cuello et al, 2007). Regarding the association between ERK1/2 and c-Fos, some in vivo studies show that in the spinal cord, ERK1/2 is required for c-Fos expression after noxious stimulation (Cruz et al, 2007;Zhang et al, 2009), whereas others illustrate c-Fos expression in the absence of ERK1/2 activation in different animal models (Ji and Rupp, 1997;Kominato et al, 2003).…”
Section: Downloaded Frommentioning
confidence: 99%